Spray-Dried Polymeric Nanoparticles for Pharmaceutics: A Review of Patents - C.R. Beck, Ruy; F. Ourique, Aline; S. Guterres, Silvia; R. Pohlmann, Adriana (Recent Patents on Drug Delivery & Formulation, 2012)
Polymeric nanoparticles have been the focus of several researches in the last three decades in diverse areas including the delivery of pharmaceutical, diagnostic and cosmetic agents. These nanocarriers are able to improve the bioavailability and intrinsic solubility of drugs, to target different agents to a specific location or to protect the agent against extrinsic factors, such as radiation and extreme pH conditions. Despite the high interest in the development of these formulations, they hold some disadvantages like the limited physicochemical stability, which hinders the scaling-up of the preparation methods. In this context, spray-drying techniques have been proposed to obtain powder compositions containing polymeric nanoparticles allowing this limited property to be circumvented. In this context, this review is focused on the latest patents related to obtaining spray-dried polymeric nanoparticles, which have been divided into three different groups, according to their approach: i) spray-drying solutions to obtain nanoparticles, ii) spray-drying emulsions/ dispersions to obtain nanoparticles, and iii) nanoparticles dried by spray-drying.
Keywords: nanoparticles